Dawru Al-Waqf al-Mu’aqqat fî al-Tamwîl al-Ijtimâ’i fî al-Mashrîfiyah al-Islâmiyah Bî Malayziyâ - Ghalia, Bouhedda; Zakariyah, Luqman; AlNajjar, Yahya Abdullah (Faculty of Shariah, Institut Agama Islam Negeri Madura, 2022)
تهدف هذه الورقة البحثة إلى دراسة "الوقف المؤقت" ودوره في تفعيل التمويل الاجتماعي في المصرفة الإسلامية بمليزيا كالدراسة الاستشراقية في ضوء مقاصد الشريعة الإسلامية. ولقد استخدمت هذه الورقة البحثية المنهج الكيفي في مباحثها المتعلقة بالـتأصيل والضبط لمفهوم الوقف المؤقت وما يتعلق به من القضايا في أبعادها الشرعية والمصرفية في ضوء مقاصد الشريعة؛ واعتمدت الدراسة في الجانب الميداني على اختيار "ماي بنك الإسلامي "كعينة تطبيقية لدراسة الموضوع في جوانبه المتعددة. وخلصت الدراسة إلى جملة من النتائج والتوصيات، من أهمّها:1) فإن الوقف المؤقت في التجربة الماليزية أنه لايزال الاهتمام به في مرحلة التشريعات النظرية في التقنين له ويحتاج إلى إيجاد آليات جديدة لتفعيله في واقع الممارسة.2) "الوقف المؤقت" النقدي آلية استشرافية يقترحها البحث في سدّ عجز التمويل الاجتماعي في منتجات الوقف المصرفي لمصرف" ماي بنك الإسلامي" كعينة مختارة في هذه الدراسة والتي تسعى إلى تحقيق خطة تنموية اجتماعية إلى تفعيله وتوسيعه. 3) النظر المقاصدي في التمويل الاجتماعي المصرفي يدعم اقتراح آلية الوقف المؤقت النقدي كوسيلة فعالة نظرا لما يحققه من مقاصد تنموية اجتماعية؛ ومنها التكافل الاجتماعي، النماء المالي، والعدالة الاجتماعية من خلال وساطة المصارف الإسلامية للمصارف الإسلامية كفاءة في أن يكون لها دور مهم في الوساطة بين مصادر التمويل الاجتماعي التطوعي والطبقات الاجتماعية المحرومة وما يؤهلها لذلك كونها مؤسسات لها إمكانيات في نظم الإدارة والحوكمة. / This research paper aims to study the "temporary endowment" (Waqf Muaqqat) and its role in activating social financing in Islamic banking in Malaysia, such as the oriental study in the light of the purposes of Islamic law. This article has adopted the qualitative method in its research which correlates to the theorization and regulation of the concepts of the issues in hand in their different dimensions which is jurisprudence, Maqasid, and banking. For the case study “Maybank Islamic” has been selected for viewing and assessing the various aspects related to the said topic. The study also included interviews with some experts of Islamic banking in Malaysia. The study has stemmed the following conclusions and recommendations, which are as follows: 1) Islamic banks have a significant role in intermediating between both the sources of voluntary social financing and the deprived classes of the society, 2) Bank endowments (Waqf) through May Islamic Bank has shown substantial contributions in the social financing. The study further has found many possibilities of making it more effective and expand its reach using the tool of temporary endowment, 3) Temporary bank endowment contributes to achieving the objectives of social cooperation (Takaful), financial growth, and social justices through the medium of Islamic banks. The article concludes by stating that social financing of banks needs various other tools of temporary endowment (Waqf Muaqqat) to help the deprived classes and to extend its reach to meet the requirements for a comprehensive and inclusive development of the overall society.